2009
DOI: 10.3109/10253890902787826
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the serotonin transporter gene modulates brain and physiological responses to acute stress in Japanese men

Abstract: A short (S) variant, compared to a long (L) variant, of the promoter region of the serotonin transporter gene-linked polymorphic region (5HTTLPR) has been related to emotional hyper-reactivity. We tested whether the 5HTTLPR could modulate acute stress responses in the brain and, the cardiovascular and neuroendocrine systems. Ten Japanese male participants carrying double copies of the S alleles and 10 Japanese males carrying S and L alleles conducted a mental arithmetic task, and their regional cerebral blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 65 publications
(70 reference statements)
1
18
0
Order By: Relevance
“…Ohira et al . also reported that Japanese individuals with the s/s genotype of the 5-HTTLPR showed greater blood pressure reactivity to an acute stressor than those with the s/l or l/l genotype 6 . Taken together, it is speculated that s/s individuals in Japanese are prone to become depression by psychological stress.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Ohira et al . also reported that Japanese individuals with the s/s genotype of the 5-HTTLPR showed greater blood pressure reactivity to an acute stressor than those with the s/l or l/l genotype 6 . Taken together, it is speculated that s/s individuals in Japanese are prone to become depression by psychological stress.…”
Section: Discussionmentioning
confidence: 91%
“…Many studies have suggested an association between the 5-HTT genotype and physiological reactivity to acute stressors 6, 7 . Gotlib et al .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a possible association of the 5-HTTLPR with youth depression has been traced in numerous studies [42-54]. Most studies were based on Caucasian populations, except for a few examining the Japanese general population [55,56]. No significant genotypic association of the 5-HTTLPR polymorphism with depression in a Japanese pediatric population, particularly in patients who have adverse parental environment, was operationalized as the mothers’ history of recurrent major depressive disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Further, each immune measure showed a wide range of reactivity to school entry, variability in immune response that has now been broadly documented (e.g., (14, 21, 43, 45, 46)). Such differences are likely multi-factorial in origin and may be affected by gene polymorphisms (47, 48), experiences of social subordination (49), and coping styles (50). …”
Section: Discussionmentioning
confidence: 99%